2002
DOI: 10.1177/002215540205000507
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-specific Localization of Human Cardiac S1P Receptors

Abstract: S U M M A R Y Sphingosine 1-phosphate (S1P), which derives from the metabolism of sphingomyelin, is mainly synthesized, stored, and released from platelets after activation by physiological and pathophysiological events. S1P acts in cardiovascular tissues through cell surface G-protein-coupled receptors of the endothelial differentiation gene (EDG) family, i.e., EDG1, EDG3 and EDG5. The aim of the present study was to assess the precise distribution of EDG1, EDG3, and EDG5 receptors expressed in human cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 33 publications
10
78
3
Order By: Relevance
“…Studies have shown that S1P1 is highly expressed in atrial, septal and ventricular cardiomyocytes, and in the endothelial cells of cardiac vessels in humans [4,5]. Furthermore, S1P1 is considered to …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that S1P1 is highly expressed in atrial, septal and ventricular cardiomyocytes, and in the endothelial cells of cardiac vessels in humans [4,5]. Furthermore, S1P1 is considered to …”
Section: Discussionmentioning
confidence: 99%
“…The study period was a maximum of 44 days for each subject, comprising a 21-day screening period, a 12-day treatment period (days [1][2][3][4][5][6][7][8][9][10][11][12] and an end of study assessment 10 days after the last treatment day (day 22). Sub-E. Legangneux et al…”
Section: Study Period and Drug Administrationmentioning
confidence: 99%
“…The demonstration in vivo that a non-selective S1P receptor agonist active on S1P 3 induces bradycardia in wildtype mice that is abolished in S1P 3 Ϫ/Ϫ mice provides further support for the role of S1P 3 in the heart. Both S1P 1 and S1P 3 are expressed on cardiac endothelium and perhaps myocardium (42), yet deletion of S1P 3 alone abolishes the bradycardia induced by non-selective S1P receptor agonists, and an S1P 1 -selective agonist does not induce bradycardia. These data provide evidence that the pleiotropicity of S1P function has, at least in the specific instances of lymphocyte recirculation and bradycardia, a basis in differential receptor subtype usage in the cardiac and lymphatic systems, respectively.…”
Section: Figmentioning
confidence: 99%
“…Further, S1PþJTE013 treatment resulted in a significant expansion in venules relative to all comparative treatments, including FTY720. This discrepancy in arterial and venous responses to the same compound could be explained by differences in receptor expression patterns between the two vessel types, 35,36 but further validation is required. Unexpectedly, S1PþJTE013 delivery did not significantly increase functional length density; in fact, length density significantly decreased over the course of 7 days compared to FTY720 treatment, although not statistically different than treatment with S1P alone.…”
mentioning
confidence: 99%